Fiscal federalism in India - Vithal, B.P.R. (New Delhi, 2001)
This volume reviews Centre-State relations in India and the evolution of this relationship since the 1950s, as seen from the perspective of the ten Finance Commissions.
Keywords: Fiscal policy